Cold War on CNN, Part 11: Vietnam 1954-1968 (United Kingdom : Jeremy Isaacs Productions, 1998)
It was a conflict that devastated one nation and divided another. Vietnam brought a new dimension to the Cold War -- and forced the United States to rethink its goals in the superpower rivalry.
Keywords: United Kingdom